The global economic burden of diabetes in adults aged 20-79 years: a cost-of-illness study - Bommer, Christian; Bärnighausen, Till (The lancet. Diabetes & Endocrinology, 2017)
Summary Background Differences in methods and data used in past studies have limited comparisons of the cost of illness of diabetes across countries. We estimate the full global economic burden of diabetes in adults aged 20-79 years in 2015, using a unified framework across all countries. Our objective was to highlight patterns of diabetes-associated costs as well as to identify the need for further research in low-income regions. Methods Epidemiological and economic data for 184 countries were used to estimate the global economic burden of diabetes, regardless of diabetes type. Direct costs were derived using a top-down approach based on WHO general health expenditure figures and prevalence data from the 2015 International Diabetes Federation Diabetes Atlas. Indirect costs were assessed using a human-capital approach, including diabetes-associated morbidity and premature mortality. Findings We estimate the global cost of diabetes for 2015 was US$1·31 trillion (95% CI 1·28-1·36) or 1·8% (95% CI 1·8-1·9) of global gross domestic product (GDP). Notably, indirect costs accounted for 34·7% (95% CI 34·7-35·0) of the total burden, although substantial variations existed both in the share and the composition of indirect costs across countries. North America was the most affected region relative to GDP and also the largest contributor to global absolute costs. However, on average, the economic burden as percentage of GDP was larger in middle-income countries than in high-income countries. Interpretation Our results suggest a substantial global economic burden of diabetes. Although limited data were available for low-income and middle-income countries, our findings suggest that large diabetes-associated costs are not only a problem in high-income settings but also affect poorer world regions. Funding None.